Generative AI. (Insights you need from Harvard Business Review., 2024)
"The world is stunned and transfixed by the marvel (and possible menace) of ChatGPT and other generative AI tools. It's clear that they will transform the business landscape-exactly when and how much are still to be seen. Meanwhile, your smartest competitors already navigating the risks and reaping the rewards of this new technology. They're trying out new business models around generating text and code at astonishing speed. They're automating customer interactions in ways that were never before possible. And they're augmenting human creativity innovate in new ways. How can you take advantage of generative AI and avoid having your business disrupted? Generative AI: The Insights You Need from Harvard Business Review will help you understand the potential of this new technology, pick the right generative AI projects, and reinvent your business for the new age of AI"--